2017
DOI: 10.1093/femsec/fix048
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling microbial ecology of industrial-scale Kombucha fermentations by metabarcoding and culture-based methods

Abstract: Kombucha, historically an Asian tea-based fermented drink, has recently become trendy in Western countries. Producers claim it bears health-enhancing properties that may come from the tea or metabolites produced by its microbiome. Despite its long history of production, microbial richness and dynamics have not been fully unraveled, especially at an industrial scale. Moreover, the impact of tea type (green or black) on microbial ecology was not studied. Here, we compared microbial communities from industrial-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
203
2
24

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(238 citation statements)
references
References 50 publications
9
203
2
24
Order By: Relevance
“…Comparing to Kombucha samples analyzed in other studies, the Turkish Kombucha samples have relatively lower microbial diversity in the sampling days which could be caused by previous long periods of fermentation or DNA isolation method. When we compared our taxonomic analysis results with previously reported NGS‐based Kombucha studies (Chakravorty et al., ; Coton et al., ; De Filippis et al., ; Marsh et al., ; Reva et al., 2015), we observed a high concordance with Marsh et al. () which applied a very similar DNA isolation method and found ≥90% Gluconacetobacter , which formerly included Komagataeibacter (Yamada et al., ), and ≥95% Zygosaccharomyces at day 3 and day 10.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Comparing to Kombucha samples analyzed in other studies, the Turkish Kombucha samples have relatively lower microbial diversity in the sampling days which could be caused by previous long periods of fermentation or DNA isolation method. When we compared our taxonomic analysis results with previously reported NGS‐based Kombucha studies (Chakravorty et al., ; Coton et al., ; De Filippis et al., ; Marsh et al., ; Reva et al., 2015), we observed a high concordance with Marsh et al. () which applied a very similar DNA isolation method and found ≥90% Gluconacetobacter , which formerly included Komagataeibacter (Yamada et al., ), and ≥95% Zygosaccharomyces at day 3 and day 10.…”
Section: Resultssupporting
confidence: 77%
“…Due to its claimed positive effects on human health, a number of research studies have been conducted on the biochemical characteristics, microbiology, toxicity, cellulose production, and fermentation dynamics of this beverage (Greenwalt, Steinkraus, & Ledford, 2000;Jayabalan et al, 2014;Rosma, Karim, & Bhat, 2012;Sreeramulu, Zhu, & Knol, 2000). Until recently, studies on the microbial ecology of Kombucha have determined the bacterial and fungal diversity through culture-based methods or sequencing of the phylogenetic marker genes (Chakravorty et al, 2016;Coton et al, 2017;De Filippis, Troise, Vitaglione, & Ercolini, 2018;Marsh, O'Sullivan, Hill, Ross, & Cotter, 2014;Reva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria commonly found in kombucha include the acetic acid bacteria belonging to the genera, Acetobacter, Gluconacetobacter , and Gluconobacter , as well as LAB. Most of the yeasts associated with kombucha are species of Saccharomyces , although other yeast genera may also be present (Teoh et al, 2004; Coton et al, 2017). While this product is now widely consumed, and manufacturers promote the presence of live microorganisms on product labels, there are few published data on the levels of microbes present in retail products.…”
Section: General Survey Resultsmentioning
confidence: 99%
“…While this product is now widely consumed, and manufacturers promote the presence of live microorganisms on product labels, there are few published data on the levels of microbes present in retail products. One recent study reported both bacterial and yeast counts for two kombucha products that were produced under industrial manufacturing conditions (Coton et al, 2017). In general, acetic acid bacteria levels ranged from 10 6 to 10 7 cfu/mL at the end of the fermentation, and similar counts were reported for LAB and total aerobic bacteria.…”
Section: General Survey Resultsmentioning
confidence: 99%
“…Oenococcus oeni is the predominant species in wine and in apple cider and it was also recently reported in kombucha fermentation (Coton et al . ), but it is rarely detected in other environments. Multilocus sequence typing analyses have shown that the species comprises two major lineages, named groups A and B, and probably at least one additional group C (Bilhere et al .…”
Section: Introductionmentioning
confidence: 99%